Prioritization of soil and water conservation using geospatial technology - Janani, N; Dharumarajan, S (Indian Farming, 2020)
In recent times, when summer hits India, most of the areas face shortage of rainfall, stipulation of drinking water and face drought. In some places there is an enormous amount of downpour which leads to flood. Conservation practises must be carried out during excess to overcome the drought in the remaining period. To analyse these types of major parameters with respect to time period, factors and renovation, remote sensing and GIS tool can be used.